A Student Serang Regency General Election Commission Socialization Level of First-Time Voter Participation in the 2024 Legislative Election Case Study of the Serang Regency General Election Commission Office - Heni Hardiyanti; Sulkiah Hendrawati; Wahyudi Wahyudi (Journal of Innovative and Creativity, 2025)
This study aims to examine the form and implementation of outreach activities conducted by the Serang Regency General Elections Commission (KPU) in preparation for the 2024 Legislative Elections. The study uses a normative method combined with an empirical approach, including interviews with KPU officials and field data collection. The study focuses on the effectiveness of outreach strategies, both directly through the "KPU Goes to School" program and indirectly through social media and digital content. Research findings indicate that the outreach strategy implemented by the Serang Regency General Elections Commission (KPU) has adapted to technological developments and the communication patterns of the younger generation. The use of digital platforms such as Instagram, TikTok, and YouTube has proven effective in engaging first-time voters. However, several challenges remain, including budget constraints, lack of support from some schools, and unequal access to digital infrastructure across the region. Factors supporting the effectiveness of the outreach program include regulations from the central government, the active involvement of democracy volunteers, and established collaborations with several schools. The tangible impact of this outreach strategy is evident in the increased participation rate of first-time voters, which reached 71% of the total number of first-time voters on the Serang Regency Permanent Voter List (DPT). This achievement demonstrates that an approach tailored to the characteristics of the younger generation can encourage their more active involvement in the democratic process. Based on the research findings, it is recommended that the General Elections Commission (KPU) conduct regular evaluations of its outreach methods, increase the capacity of democracy volunteers, and strengthen collaboration with educational institutions and digital communities. Furthermore, increasing budget allocation and providing adequate technological infrastructure are also important considerations to ensure more inclusive and high-quality political participation among first-time voters in the future.